Comparative Analysis of Market Performance and Capital Structure between Consumer Financing and Investment Financing Companies Listed on the Indonesia Stock Exchange - A. Reski Almaida Dg Macenning (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2025)
This study aims to analyze the differences in financial performance between consumer financing and investment financing companies listed on the Indonesia Stock Exchange (IDX) for the period 2021–2025. The financial ratios used include Earnings per Share (EPS), Book Value per Share (BVPS), Price Earnings Ratio (PER), Price to Book Value (PBV), and Debt to Equity Ratio (DER). This research employs a quantitative comparative approach, utilizing secondary data from the annual financial reports of financing companies listed on the IDX. Data analysis was conducted using the Independent Sample t-test to determine significant differences between the two groups of companies. The results indicate no significant difference in EPS (p-value 0.258) and PER (p-value 0.322), suggesting that the ability to generate profit and market perception towards earnings growth are relatively similar between the two groups. However, significant differences were found in Book Value per Share (p-value 0.066) and PBV (p-value 0.007), indicating that the market value of investment financing companies tends to exceed their book value. Additionally, consumer financing companies tend to have higher DER ratios, reflecting greater reliance on debt. These findings imply that although the financial structure and profitability of both sectors are relatively balanced, market perception is more influenced by trust in long-term prospects and the quality of managed financing assets. Furthermore, these results offer implications for investors and management in considering capital structure and market value as bases for investment decisions and funding strategies in the financing sector.